Implentasi App Google Classroom In Online Learning IPA The Pandemic Covid-19 - nurkhilal; Irham Huspa K. Siregar; Kurnia Putra (CV. AFDIFAL MAJU BERKAH, 2021)
The objectives to be achieved in this research are: (1) to know the implementation of google apps classroom; (2) to determine the creativity of teachers in implementing google apps classroom; (3) the constraints experienced by teachers in implementing google apps classroom; and (4) the efforts done by the teacher to overcome the obstacles in implementing app google classroom. The research method uses a qualitative approach with descriptive method. Data sources in this study include primary sources and secondary sources. The informant in this research is the head of the school, waka curriculum, SCIENCE teacher, and eight students in SMK negeri 1 Rantau Utara. Data collection techniques used were interviews and documentation. The technique of data analysis consists of data reduction, data presentation, and conclusion. While checking the validity of data using triangulation of sources. The research results revealed that: (1) the implementation of google apps classroom shows three teachers using the app matches the policy of the head of the school; (2) the creativity of teachers in implementing google apps classroom of the three teachers vary in their creativity; (3) the Constraints experienced by teachers in implementing the application google classroom is influenced by the lack of communication to students, and signal; and (4) the Efforts done by the teacher to overcome the obstacles in implementing google apps classroom with communication to students, parents, homeroom, and others that play a role in the process of learning online